A two-photon fluorescent probe for detecting endogenous hypochlorite in living cells. Issue 14 (11th March 2015) - Wang, Xunming; Wang, Xiaohui; Feng, Yan; Zhu, Manzhou; Yin, Hang; Guo, QingXiang; Meng, Xiangming
Abstract : A highly selective two-photon fluorescent probe (HQ ) for endogenous hypochlorite (ClO − ) was developed. Abstract : A novel two-photon fluorescent probe (HQ ) for hypochlorite (ClO − ) has been developed based on specific ClO − -promoted oxidation of a CN bond. The probe shows linear fluorescence responses to ClO − with 23.5-fold enhancement. Two-photon fluorescence detection signals ofHQ to ClO − were observed with high selectivity and sensitivity. The good biocompatibility guaranteed the use ofHQ to detect intracellular ClO − under two-photon excitation. Moreover, HQ has been successfully applied to monitor the endogenously produced hypochlorite in living cells (BV-2 ) stimulated by lipopolysaccharide (LPS).HQ provides a new ClO − detection agent for the discovery of pharmacological microglia modulators by high-throughput screening.